Cholesterol crystal embolisation to the alimentary tract. (February 1996) - Moolenaar, W; Lamers, C B
Abstract : The features of cholesterol crystal embolisation (CCE) to the alimentary tract were studied by retrospective analysis of the clinical and pathological data of 96 patients (70 men, 26 women, mean age 73.8 (58-95) years) with this diagnosis in the Dutch national pathology information system (Pathologisch Anatomisch Landelijk Geautomatiseerd Archief (PALGA)) from 1973-92. In the 96 patients, 130 CCE sites were found throughout the alimentary tract, mostly in the colon (42.3%). Most patients had a history of atherosclerotic disease and presented with abdominal pain, diarrhoea, or gastrointestinal bleeding, sometimes after surgical or radiological vascular procedures. A number were taking oral anticoagulant treatment. The diagnosis of CCE had been considered before the histological diagnosis in only 11 patients. In the remaining cases, ischaemic colitis, tumour, and inflammatory bowel disease were suggested in the differential diagnosis. A premortem diagnosis of CCE was made in 70.8% of the cases. In 24 of the 35 necropsy examinations, CCE seemed to be directly or indirectly related to the cause of death. It is concluded that in this unselected, homogenous group of patients, CCE sites were most frequently found in the colon. They generally presented with abdominal pain, diarrhoea, and gastrointestinal blood loss. CCE often mimicked common gastrointestinal disease, leading to incorrect diagnosis.